2018
DOI: 10.1371/journal.pone.0196843
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of mammalian angiogenesis by neolignans derived from soybean extracellular fluids

Abstract: Excessive or insufficient angiogenesis is associated with major classes of chronic disease. Although less studied, small molecules which can promote angiogenesis are being sought as potential therapeutics for cardiovascular and peripheral arterial disease and stroke. Here we describe a bioassay-directed discovery approach utilising size exclusion and liquid chromatography to purify components of soybean xylem sap that have pro-angiogenic activity. Using high resolution accurate mass spectrometry and nuclear ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…7 As neolignans are a diverse group of chemical structures present in several plant families and responsible for multiple biological activities, we chose to investigate the trypanomicidal potential of a set of neolignans. [8][9][10][11] Some studies [12][13][14] have reported the importance of neolignans as promising compounds in the treatment against T. cruzi.…”
Section: Introductionmentioning
confidence: 99%
“…7 As neolignans are a diverse group of chemical structures present in several plant families and responsible for multiple biological activities, we chose to investigate the trypanomicidal potential of a set of neolignans. [8][9][10][11] Some studies [12][13][14] have reported the importance of neolignans as promising compounds in the treatment against T. cruzi.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Screening plant extracts for such properties is an emerging area of interest and the rat aortic ring model and related assays have proven useful in identifying natural products that can modulate angiogenesis. 2 , 3 By such means, various extracts of soybean (particularly the xylem sap) were evaluated recently, and two proangiogenic principals were isolated. 3 Although only small quantities of these materials were obtained, 1 H and 13 C NMR spectroscopic as well as mass spectral analyses suggested that these are one or other of the neolignans 1 or ent - 1 and 2 or ent - 2 .…”
Section: Introductionmentioning
confidence: 99%
“… 3 Although only small quantities of these materials were obtained, 1 H and 13 C NMR spectroscopic as well as mass spectral analyses suggested that these are one or other of the neolignans 1 or ent - 1 and 2 or ent - 2 . 3 The racemic forms of these compounds have previously been isolated from various other plant sources and shown to exhibit a range of biological effects. 4 They are almost certainly produced in vivo through peroxidase-mediated radical coupling of coniferyl alcohol, and optically enriched forms of them (but of undefined absolute stereochemistry) have been generated by enzymatic dehydrogenative coupling of this monomer using cell-free extracts of a producing organism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations